2019
DOI: 10.1111/jcmm.14790
|View full text |Cite
|
Sign up to set email alerts
|

l‐tetrahydropalmatine suppresses osteoclastogenesis in vivo and in vitro via blocking RANK‐TRAF6 interactions and inhibiting NF‐κB and MAPK pathways

Abstract: Bone homeostasis is delicately orchestrated by osteoblasts and osteoclasts. Various pathological bone loss situations result from the overactivated osteoclastogenesis. Receptor activator of nuclear factor κB ligand (RANKL)‐activated NF‐κB and MAPK pathways is vital for osteoclastogenesis. Here, we for the first time explored the effects of l‐tetrahydropalmatine (l‐THP), an active alkaloid derived from corydalis, on the formation and function of osteoclasts in vitro and in vivo. In RAW264.7 cells and bone marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In addition, THP activates the K ATP channel and plays a role in vascular relaxation, and promotes angiogenesis by regulating the sequence of citrulline-to-arginine flux, arginine biosynthesis, and VEGFR2 expression in endothelial cells ( Cui et al, 2021 ), as shown in Figure 6 . Furthermore, THP can inhibit osteoclast formation in a dose-dependent manner and has no cytotoxicity at a concentration lower than 19.00 μg/ml ( Zhi X. et al, 2020 ). In vitro experiments, THP suppressed early osteoclast differentiation, downregulated the transcription level of osteoclast-related genes, and impaired the function of osteoclasts in bone marrow monocytes cells and mouse leukemic monocyte/macrophage cell line RAW264.7 cells.…”
Section: Pharmacological Activities Of Tetrahydropalmatinementioning
confidence: 99%
“…In addition, THP activates the K ATP channel and plays a role in vascular relaxation, and promotes angiogenesis by regulating the sequence of citrulline-to-arginine flux, arginine biosynthesis, and VEGFR2 expression in endothelial cells ( Cui et al, 2021 ), as shown in Figure 6 . Furthermore, THP can inhibit osteoclast formation in a dose-dependent manner and has no cytotoxicity at a concentration lower than 19.00 μg/ml ( Zhi X. et al, 2020 ). In vitro experiments, THP suppressed early osteoclast differentiation, downregulated the transcription level of osteoclast-related genes, and impaired the function of osteoclasts in bone marrow monocytes cells and mouse leukemic monocyte/macrophage cell line RAW264.7 cells.…”
Section: Pharmacological Activities Of Tetrahydropalmatinementioning
confidence: 99%
“…Paeoni orin treatment of osteoporosis can be divided into two general directions: inhibiting osteoclast activity [70] and improving osteoblast activity [71,72], It slows bone resorption by inhibiting osteoclast activity and promotes bone formation by increasing osteoblast activity. Corydalis Yanhusuo contains Tetrahydropalmatine, Experimental studies in vivo and in vitro have shown that Tetrahydropalmatine inhibits osteoclast formation by inhibiting NF-κB and MAPK pathways [73]. Coicis Semen extract has been shown to promote osteoblast proliferation and effectively relieve osteoporosis in animals [73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that l-tetrahydropalmatine, a major compound purified from this formula, significantly suppresses the receptor activator of nuclear factor κB ligand (RANKL)-activated NF-κB and MAPK pathway. 24 This pathway involves the inhibition of osteoclastogenesis and regulation of osteoblast differentiation and osteogenic formation. 25 The present study also showed that use of Bei-Mu and Da-Huang may lessen the risk of fracture among RA subjects.…”
Section: Discussionmentioning
confidence: 99%